Valentine's day - Doherty, Berlie (London: Catnip, 2009)
Anna has gone to live with Grandpa Bill and Nanny Jean at Peak Dale Farm. There are sheep, cows, chickens and an old pony, but best of all there's a white Charolais calf called Valentine and he's Anna's best friend. When Granny Jean enters them into the Hope Show they'll both need to be on their best
Keywords: Children's stories